DEPRESSION AND ACCULTURATION IN MEXICAN AMERICAN AND EUROPEAN AMERICAN WOMEN - Masten, William G.; Asidao, Christine S.; Jerome, Wanda W.; Mosby, Laura; Cadwell-Colbert, A. Toy; Medina, Margarita Y.; Hernández, Gonzalo; Chapman, Rae; Kirilla, Carmen; Ervin, Staussa (Anales de Psicología / Annals of Psychology, 2004)
The objective of this paper was to determine the relationship between depression and acculturation among Mexican American and European American women. The participants included 76 Mexican American and European American women from Kansas City. Depression was measured by the Center of Epidemiological Studies Depression Scale and acculturation was determined by the Olmedo Acculturation Inventory. The results support existing research that indicates scores on acculturation for European Americans were significantly higher than scores for Mexican Americans, and that there were significantly higher acculturation scores for Mexican Americans from first to third generation. This study further supports past findings that indicate scores on depression for Mexican American women were higher than those for European American women. Depression scores were not influenced by demographic differences, but acculturation scores were. In addition, there was no significant relationship between acculturation and depression.